2004
DOI: 10.1245/aso.2004.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of High-Dose-Rate Intracavitary Brachytherapy With the MammoSite Applicator in Patients With Early-Stage Breast Cancer

Abstract: Most acute skin toxicities were mild. Our infection rate was higher than in prior studies that used interstitial brachytherapy. Cosmesis was good to excellent in most patients. Breast brachytherapy with the MammoSite catheter was well tolerated; further investigations of breast brachytherapy with this system are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…2 Several radiation-induced skin effects have been reported in the literature for MammoSite treatments. [5][6][7][8][9][10][11][12][13] With the advent of several new intracavitary APBI devices that claim to modify the dose distribution and reduce the exit skin dose, it is particularly important to quantify the actual skin doses received. Most brachytherapy treatment planning systems ͑TPSs͒ calculate dose using the formalism proposed by the American Association of Physicists in Medicine Task Group 43 ͑TG-43͒, which assumes a homogeneous water medium.…”
Section: Introductionmentioning
confidence: 99%
“…2 Several radiation-induced skin effects have been reported in the literature for MammoSite treatments. [5][6][7][8][9][10][11][12][13] With the advent of several new intracavitary APBI devices that claim to modify the dose distribution and reduce the exit skin dose, it is particularly important to quantify the actual skin doses received. Most brachytherapy treatment planning systems ͑TPSs͒ calculate dose using the formalism proposed by the American Association of Physicists in Medicine Task Group 43 ͑TG-43͒, which assumes a homogeneous water medium.…”
Section: Introductionmentioning
confidence: 99%
“…Czas obserwacji chorych po brachyterapii śródjamowej typu MammoSite jest znacznie krótszy niż po tradycyjnej brachyterapii śródtkankowej z użyciem wielu aplikatorów i wynosi 1-4 lat, a odsetek wznów miejscowych mieści się w granicach 0-5% [16][17][18][19][20][21][22][23][24]. W największym z badań (Mammosite Registry Trial), obejmującym 1449 chorych, odsetek wznów miejscowych po 5 latach wynosił 3,6% [25].…”
Section: Wyniki Badań Nad Apbi Bez Randomizacjiunclassified
“…The positive features of balloonbased breast brachytherapy are well described in the article by Dickler et al (7), but there are some limitations associated with this technique and problems have been noted in early reports. For example, Harper et al (10) described a 13% catheter leak or balloon rupture rate and Richards et al (11), reported a 16% rate of infection. Although these may represent the learning curve associated during an initial experience with a new technique, they still must be compared to the low technical failure and infection rates observed with interstitial breast brachytherapy (12).…”
mentioning
confidence: 99%